Glycemic Index and Load of Selected Ethiopian Foods: An Experimental Study - Nebiyu Dereje; Gadise Bekele; Yemisrach Nigatu; Yoseph Worku; Roger P. Holland (Journal of Diabetes Research)
Background. Determining the glycemic index and load of foods has significant impact on meal planning for diabetes. However, there is no data on the glycemic index (GI) and glycemic load (GL) of Ethiopian foods. Therefore, the aim of this study was to analyze the glycemic index and glycemic load of Teff Injera, Corn Injera, and White Wheat Bread. Methods. Experimental study design was conducted among selected healthy adults. Teff Injera, Corn Injera, and White Wheat Bread were selected as test foods for the study, and glucose was used as the reference food. The postprandial glucose concentrations in the blood were recorded at 0, 15, 30, 45, 90, and 120 minutes. The relative glycemic index of each food was calculated, and the presence of statistical difference in glycemic index among the three foods was analyzed. Results. The mean age of the participants was 23 years (±1.6 years). The glycemic indexes of Teff Injera, White Wheat Bread, and Corn Injera were 36 (low), 46 (low), and 97 (high), respectively, and the glycemic loads were 7 (low), 14 (moderate), and 22 (high), respectively. There was a significant difference in glycemic index and load among the three food items (p<0.001). Teff Injera had a much lower glycemic index and load compared with Corn Injera (p<0.001) and White Wheat Bread (p=0.03). Conclusions. Teff Injera and White Wheat Bread have low glycemic index and are recommended to be consumed by diabetic patients, whereas Corn Injera has high glycemic index and is not recommended for diabetic patients. Therefore, Teff Injera should be considered globally in the dietary modification programs for diabetes.